EKSPLORASI PENGALAMAN KELOMPOK PEDULI KUSTA DI MASA PANDEMI : FOCUS GROUP DISCUSSION - Aditya, Ronal Surya; Yusuf, Ah; Soelistyowati, Endang (Jurnal Keperawatan Terapan, 2021)
Abstract: Objectives: To explore the experience of leprosy care groups during a pandemic Method Phenomenological approach with focus group discussion. 15 respondents with purposive sampling technique. The analysis in Collaizi is simple, clear and detailed enough to be used in this research. Results Consists of 3 themes, namely: activity restrictions, programs cannot run, lack of mastery of technology and produces 8 sub-themes, namely: less than optimal coordination, limited activities, fear of gathering, restrictions on gathering rules, all online, insufficient power, difficult signal, HP for school children. Conclusion the pandemic period is a difficult time for leprosy care groups, so the rules, lack of technology and lack of information related to technology make the leprosy care group program stagnant. Suggestion it is necessary to form a small group to support the program, as well as socialize the application for leprosy groups Abstrak: Tujuan: Mengeksplorasi pengalaman kelompok peduli kusta di masa pandemic. Metode Pendekatan fenomenologi dengan diskusi kelompok terfokus. 15 responden dengan teknik purposive sampling. Analisis dalam Collaizi cukup sederhana, jelas dan rinci untuk digunakan dalam penelitian ini. Hasil terdiri dari 3 tema, yaitu pembatasan aktifitas, program tidak bisa berjalan, kurangnya penguasaan teknologi dan menghasilkan 8 subtema, yaitu koordinasi kurang optimal, kegiatan dibatasi, takut berkumpul, aturan pembatasan berkumpul, semua serba online, kuata tidak mencukupi, susah sinyal, HP untuk anak sekolah. Kesimpulan masa pandemic merupakan masa sulit bagi kelompok peduli kusta, sehingga aturan, kurangnya teknologi dan kurangnya informasi terkait teknologi membuat program kelompok peduli kusta stagnan. Saran perlu dibentuk kelompok kecil untuk mendukung program, serta sosialisasi aplikasi untuk kelompok kusta.